Avaliação dos padrões de vitalidade neonatal, hemogasometria e eletrocardiografia em equinos da raça Paint Horse - Cruz, Raíssa Karolliny Salgueiro [UNESP] (2014)
Clinical evaluations of newborns, as well as defining the therapeutic decision, represent significant challenges to the veterinarian. The aim of this study was to describe the patterns of neonatal vitality and biochemistry in horses breed Paint Horse eutocia born in the first 48 hours of life. 20 neonates at birth and were evaluated 10 minutes after delivery with Apgar modified. Laboratory (blood gas, electrolytes, lactate, glucose and cortisol) and electrocardiographic evaluations were performed immediately after birth (M0) and four (M1), eight (M2), 12 (M3), 16 (M4), 20 (M5 ), 24 (M6) 36 (M7) and 48 hours (M8) after birth. At Apgar score, there was statistical difference between the analyzed time points (p <0.001), with an average at birth, 7.80 ± 0.89, and 10 minutes, 8.35 ± 0.99. During the 48 hours postpartum, body temperature showed a progressive increase. Laboratory parameters such as lactate, sodium, potassium, glucose, anion gap and cortisol changed significantly in the time points analyzed. No statistical differences were found between blood gas parameters. In the electrocardiogram, there was progressive decrease in QT interval duration and the amplitude and duration of the T wave In conclusion, neonatal foals showed significant electrolyte, biochemical and electrocardiographic changes during the first 48 hours of life, with the appropriate parameters for proposed assessment of neonatal vitality. The common occurrence of clinical and laboratory abnormalities in apparently healthy newborn foals emphasizes the need to conduct regular clinical examinations and laboratory reference values at different ages. The data found subsidize the fundamental aspects of neonatal physiology and the variability of the clinical parameters in foals eutocia and serve as a basis for clinical decision making in cases of dystocia